On θ−GN−Precontinuous Functions in Grill Topological Spaces - Almuntaser, Maged Abdulwahab; Saif, Amin (Enhanced Knowledge in Sciences and Technology, 2022)
In this paper, we introduced and investigated the notions of θ−GN−preclosed sets in grill topological space, θ−GN−precontinuous function and strongly θ−GN−precontinuous function. Furthermore, we studied the relations between the θ−GN−precontinuous and other known continuous function. They will be introduced in grill topological spaces by using the GN−preopen sets.